2015
DOI: 10.19173/irrodl.v16i3.1951
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ goal profiles and their learning patterns over an academic year

Abstract: The present study aimed to examine distance learners' goal profiles and their contrasting patterns of learning and achievements at three different points during an academic year, i.e. in the beginning of the course in relation to learners' general orientations to learning, at the middle of the course in relation to learners' completion of an assignment, and towards the end of the course in relation to learners' preparation for course examination. Two hundred seventy-six adult distance learners completed three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…These findings may reflect that, first, the students may generally consider online learning practices as being independent and self-regulated and then endorse mastery-related goals as the most crucial orientations (e.g. Ng, 2015 ; Vanslambrouck et al 2018 ). Second, it is possible that the long-term usage of online learning in the current situation may not be familiar to the Taiwanese students, even though they had relevant online learning experience before.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings may reflect that, first, the students may generally consider online learning practices as being independent and self-regulated and then endorse mastery-related goals as the most crucial orientations (e.g. Ng, 2015 ; Vanslambrouck et al 2018 ). Second, it is possible that the long-term usage of online learning in the current situation may not be familiar to the Taiwanese students, even though they had relevant online learning experience before.…”
Section: Discussionmentioning
confidence: 93%
“…Kaplan and Maehr ( 2007 ) claimed that different goal orientations may be related to various patterns of cognition, affection, and behavior. Relevant online learning research (e.g., Ng 2015 ; Remedios and Richardson 2013 ) also suggested that, in general, learners with mastery goals tend to express adaptive learning patterns such as higher levels of self-efficacy, persistence, deeper engagement, as well as frequent usage of cognitive and regulatory strategies. However, relevant studies adopting achievement goal theory in the line of online learning research are still scarce, and this field of research is still in its nascent stage.…”
Section: Literature Reviewmentioning
confidence: 99%